Child, maternal and household-level correlates of nutritional status: a cross-sectional study among young Samoan children. Issue 7 (6th February 2017) - Choy, Courtney C; Desai, Mayur M; Park, Jennifer J; Frame, Elizabeth A; Thompson, Avery A; Naseri, Take; Reupena, Muagututia S; Duckham, Rachel L; Deziel, Nicole C; Hawley, Nicola L
Abstract: Objective: Young children are particularly vulnerable to malnutrition as nutrition transition progresses. The present study aimed to document the prevalence, coexistence and correlates of nutritional status (stunting, overweight/obesity and anaemia) in Samoan children aged 24–59 months. Design: A cross-sectional community-based survey. Height and weight were used to determine prevalence of stunting (height-for-age Z -score <−2) and overweight/obesity (BMI-for-age Z -score >+2) based on WHO growth standards. Anaemia was determined using an AimStrip Hemoglobin test system (Hb <110 g/l). Setting: Ten villages on the Samoan island of Upolu. Subjects: Mother–child pairs ( n 305) recruited using convenience sampling. Results: Moderate or severe stunting was apparent in 20·3 % of children, 16·1 % were overweight/obese and 34·1 % were anaemic. Among the overweight/obese children, 28·6 % were also stunted and 42·9 % anaemic, indicating dual burden of malnutrition. Stunting was significantly less likely among girls (OR=0·41; 95 % CI 0·21, 0·79, P <0·01) than boys. Overweight/obesity was associated with higher family socio-economic status and decreased sugar intake (OR per 10 g/d=0·89, 95 % CI 0·80, 0·99, P =0·032). The odds of anaemia decreased with age and anaemia was more likely in children with an anaemic mother (OR=2·20; 95 % CI 1·22, 3·98, P =0·007). No child, maternal or household characteristic was associated with more than one of the nutritional status outcomes, highlighting the need for condition-specific interventions in this age group. Conclusions: The observed prevalences of stunting, overweight/obesity and anaemia suggest that it is critical to invest in nutrition and develop health programmes targeting early childhood growth and development in Samoa.